Beyond Convenience: Generation Z’s Perceptions of E-Wallet Use and Its Implications for Financial Literacy and Educational Management - Umar Bain; Rahmayati (Al-Qalam Institue, 2026)
This study aims to analyze Generation Z’s perceptions of the use of e-wallets such as Touch 'n Go, GrabPay, and MAE in their daily financial activities and to examine the implications for digital financial behavior and educational management. The study uses a qualitative approach with a descriptive case study design to obtain an in-depth understanding of users’ experiences with digital payment technologies. Informants were selected through purposive sampling based on the criteria of belonging to Generation Z and actively using at least one e-wallet application. Data were collected through in-depth interviews, observation, and documentation, and analyzed using interactive analysis techniques including data reduction, data display, and conclusion drawing. The findings show that Generation Z generally has positive perceptions of e-wallet usage, particularly regarding convenience, usefulness, and the integration of digital services that facilitate efficient transactions. However, ambivalent perceptions were also identified, especially related to concerns about data security and the potential for consumptive behavior due to promotional incentives such as cashback and discounts. These findings indicate that e-wallets are perceived not only as payment tools but also as part of the digital lifestyle of Generation Z. The study highlights the importance of strengthening digital financial literacy and responsible financial behavior through educational management strategies.